2011
DOI: 10.1007/s00234-010-0834-y
|View full text |Cite
|
Sign up to set email alerts
|

Endolympathic hydrops in patients with vestibular schwannoma: visualization by non-contrast-enhanced 3D FLAIR

Abstract: Vestibular endolymphatic space can be recognized on non-contrast-enhanced 3D FLAIR. In some patients with VS, vestibular hydrops is seen; however, endolymphatic hydrops in the vestibule might not be the only responsible cause of vertigo in the patients with VS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 27 publications
0
36
1
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29][30] A FLAIR image allows the detection of subtle subarachnoid hemorrhage in the CSF space, 9 signal increases in CSF after the inhalation of oxygen, 31 and subtle compositional changes of the labyrinthine fluid (Figs. 6 and 7), 26,27,30,[32][33][34] which can be difficult to recognize on T 1 -weighted images. Heavily T 2 -weighted 3D-FLAIR has been reported to be much more sensitive than regularcontrast 3D-FLAIR.…”
Section: T 2 -Selective Inversion Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27][28][29][30] A FLAIR image allows the detection of subtle subarachnoid hemorrhage in the CSF space, 9 signal increases in CSF after the inhalation of oxygen, 31 and subtle compositional changes of the labyrinthine fluid (Figs. 6 and 7), 26,27,30,[32][33][34] which can be difficult to recognize on T 1 -weighted images. Heavily T 2 -weighted 3D-FLAIR has been reported to be much more sensitive than regularcontrast 3D-FLAIR.…”
Section: T 2 -Selective Inversion Recoverymentioning
confidence: 99%
“…72 Incidentally, endolymphatic hydrops can be recognized on non-contrast-enhanced 3D-FLAIR images due to the signal increase of the perilymph. 33 …”
Section: Vestibular Schwannomamentioning
confidence: 99%
“…The presentation of simultaneous VS and ELH on the same side in the same patient is uncommon and has seldom been described in the literature [13][14][15][16] . Although the two pathologies are most probably of independent origin and should be considered separate entities, presenting and ongoing symptoms may overlap and may cause an incorrect treatment of the cochlear disorder (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Kentala and Pyykkö, the authors retrieved information on 127 patients with VS and 243 patients with ELH and found that 38% of the VS patients had the full triad of vertigo, hearing loss and tinnitus and vertigo mimicked that in ELH in 14% of cases 19 . In a recent study to verify whether vertigo in patients with VS correlates to vestibular endolymphatic hydrops, Naganawa et al studied 15 patients with unilateral VS using a noncontrast-enhanced 3D FLAIR MRI and reported vestibular hydrops in 4/15 cases; however, no significant correlation between vertigo and hydrops was found 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a histopathologic study on 32 VSs showed cochlear pathology including endolymphatic hydrops (15). Moreover, some authors visualized vestibular endolymphatic hydrops in patients with VS by means of MRI (16).…”
Section: Discussionmentioning
confidence: 99%